Motor Competence Among Children in the United Kingdom and Ireland: An Expert Statement on Behalf of the International Motor Development Research Consortium - Gareth Stratton (Journal of Motor Learning and Development, 2022)
The United Kingdom and Ireland have a well-established research base in motor competence (MC) research, ranging from reporting and monitoring levels of MC, developing assessment tools for MC, providing innovative curriculum and intervention design to support learning and development, as well as providing advocacy for particular groups, such as those with motor impairments. This expert statement, on behalf of the International Motor Development Research Consortium, draws together what is currently known about levels of MC in the United Kingdom and Ireland as well as current approaches to intervention in both countries. Subsequently presented are recommendations for researchers and practitioners to advance the field of MC for the benefit of children and youth in the United Kingdom, Ireland, and worldwide.